Use of Recycled Asphalt and Waste Materials in Production of High-Performance Asphalt Mixtures - Rolands Izaks; Liga Gebauere; Raivis Sparans; Romans Kornisovs; Viktors Haritonovs (The Baltic Journal of Road and Bridge Engineering)
The research has been conducted to test the asphalt produced in Latvia using local mineral materials and local recycled modifiers (fiberglass, crumb rubber), as well as the recycled asphalt used in the production of high-modulus asphalt mix, which will meet the local Latvian road construction specifications and will be economically, environmentally and technically more attractive. In the theoretical part, the available sources were studied to establish a theoretical framework, assess possibilities for using recycled materials, define the concept of fiberglass, and consider its performance in asphalt mixes. During the experimental stage of the research, different asphalt mix formulas with glass fiber, crushed rubber, RAP, and other additives used to stabilize asphalt mixtures for surface and base layers were designed in the laboratory; they were compared to the reference mixes using performance tests. Then the mixtures with the best results were used in the test section of a high-intensity local road. The samples of the asphalt layers of the paved test section were tested as well. Two asphalt mixes were designed according to local Latvian road-building specifications, using fiberglass reinforcement 0.15% + 30% RAP for the base layer and crushed rubber 15% and RAP 30%+EVOFLEX CA© variable for the surface layer. The aim of the research is to offer solutions for reducing new asphalt pavement production allowing for the use of recycled asphalt mixes in local road building. The performance tests of the test asphalt mixes showed that recycled asphalt pavement fully meets the requirements of the local Latvian road-building specifications.